The Role of Guidance and Counseling Teachers on Social Interaction of Down Syndrome Students at UPT SLB E Negeri Pembina Tingkat Provinsi Sumatera Utara - Aklima, Aklima; Ginting, Rafael Lisinus (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
English: This study aims to determine the role of counseling teachers on the social interaction of children with Down syndrome at school. The subjects of this study consisted of one counseling teacher, two homeroom teachers, and two parents. This research is a qualitative research with a descriptive approach. Data collection used observation, interviews, and documentation studies. Data were analyzed using triangulation of coding techniques. The results showed that there are 12 roles of counseling teachers on their social interactions, including 8 roles that often appear are the roles of consultant, transmitter, initiator, counselor, mediator, motivator, director, and informator. 5 other roles that rarely appear are the roles of coordinator, facilitator, organizer, and evaluator. Down syndrome children can interact at school if there is a stimulus from the discipline. Indonesia: Penelitian ini bertujuan untuk mengetahui peran guru BK terhadap interaksi sosial siswa down syndrome di sekolah. Subjek penelitian ini terdiri dari satu guru BK, dua guru kelas tunagrahita, dan dua orang tua siswa. Penelitian ini merupakan penelitian kualitatif dengan pendekatan deskriptif. Pengumpulan data menggunakan observasi, wawancara, dan studi dokumentasi. Data dianalisis menggunakan triangulasi teknik koding. Hasil penelitian didapatkan bahwa ada 12 peran guru BK terhadap interaksi sosial mereka diantaranya 8 peran yang sering muncul adalah peran sebagai konsultan, transmitter, inisiator, konselor, mediator, motivator, director, dan informator. 5 peran lainnya yang jarang muncul yaitu peran sebagai koordinator, fasilitator, organisator, dan evaluator. Siswa down syndrome dapat berinteraksi di sekolah apabila adanya stimulus dari disiplin ilmu.